An opportunity lost? The declining role of authorised covert human intelligence sources in combating organised crime - Ian Stanier; Jordan Nunan (Journal of Economic Criminology)
Combatting organised crime, requires Agencies to deploy a range of collection capabilities to identify community threats, to accurately select and prioritise organised crime targets and to inform operational decision-making. Central to this effort is the ability to identify, recruit and deploy Covert Human Intelligence Sources (CHIS). It is therefore paradoxical that the United Kingdom’s CHIS authorisations have been in steep decline since the enactment of the bespoke Regulation of Investigatory Powers Act 2000 (Regulation of Investigatory Powers Scotland Act, 2000). This research seeks to critically discuss as to what are the key factors contributing to this decline. Consequently, this review suggests that the decline in CHIS authorisations are to be found in a complex configuration of factors. Two stand out as significant; i) the impact of resource reduction on CHIS operational capacity and capability, and ii) an emergence of a culture of fear and risk aversion as a constraining factor on CHIS recruitment and use.